Lewin's genes XI - Krebs, Jocelyn E.; Goldstein, Elliott S.; Kilpatric, Stephen T. (New Delhi: Jone & Bartlett, 2014)
Molecular Biology is a rapidly advancing field with a constant flow of new information and cutting-edge developments that impact our lives. Lewin$1 (Bs GENES has long been the essential resource for providing the teaching community with the most modern presentation to this dynamic area of study. Lewin"s GENES XI continues this tradition by introducing the most current data from the field, covering gene structure, sequencing, organization, and expression. A wealth of subject-matter experts, from top institutions, to provide content updates and revisions in their individual areas of study. A reorganized chapter presentation provides a clear, more student-friendly introduction to course material than ever before.s
Include bibliographical references.; Glossary 894-919p.; Index 920-940p.
Keywords: Gene regulation; Genes and chromosomes; Molecular biology; Zoology